John Carroll Brent letterbook - Brent, John Carroll, 1814-1876.
Letterbook containing Brent's outgoing letters from Washington, D.C., Paris, France, Rose Hall, Scotland, and Baltimore, Md., relating to family and business matters, his claims on the office of librarian at the Smithsonian Institution, and his editing of Daniel Brent's biography of Abp. John Carroll (1843). Family correspondents include John Carroll Brent's father, William Brent, his brothers, Henry Johnson Brent and Thomas William Brent, and his cousin, Catharine Rye Douglas. Also includes letters to Robert E. Lee and Brent's business accounts.
Editor of Washington, D.C.
Collection material in English.
Keywords: Brent, Daniel, -- 1774-1841.; Brent, Henry Johnson, -- 1811-1880 -- Correspondence; Brent, Thomas William, -- 1808-1875 -- Correspondence; Brent, William, -- 1774-1848 -- Correspondence; Carroll, John, -- 1735-1815.; Douglas, Catharine Rye -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Smithsonian Institution; Baltimore (Md.) -- Social life and customs; Paris (France) -- Social life and customs; Rose Hall (Scotland) -- Social life and customs; Washington (D.C.) -- Social life and customs; Editors